The Development of Caregivers in Providing Experiences to Develop the Intelligence Quotient (IQ) of Early Childhood Children in the Early Childhood Development Centers under Local Administrative Organizations in Chaiyaphum Province - Siphai, Sunan; Siphai, Suphi; Tongma, Suchat (Interdisciplinary Academic and Research Journal, 2023)
The decline in early childhood intelligence is mainly due to parents' lack of knowledge and understanding on how to properly raise children and lack of opportunities to learn how to be good parents, which, if parents are involved in school, will help improve their children's academic performance. Many local government organizations have important missions in early childhood education management in child development centers. Thus, the purposes of this research were to explore the teaching and learning management and the needs of the Early Childhood Development Centers under Local Administrative Organizations in Chaiyaphum Province and to develop the caregivers in organizing experiences to develop the intelligence quotient (IQ) of early childhood children in the Early Childhood Development Centers under Local Administrative Organizations in Chaiyaphum Province. The samples were divided into 2 phases. Phase 1: Twenty samples, including the heads of the Early Childhood Development Centers, the caregivers, the parents, and those involved in early childhood education under Local Administrative Organizations in Chaiyaphum Province were recruited by a purposive sampling method. Phase 2: Fifty caregivers from five Early Childhood Development Centers under Local Administrative Organizations in Chaiyaphum Province were selected by a multi-stage random sampling method. The results were as follows. (1) The teaching and learning management and the needs of the Early Childhood Development Centers: In terms of personnel, the personnel are not enough, and they do not have an early childhood education degree. The budgets for supporting the Early Childhood Development Centers are also limited. The buildings of the Early Childhood Development Centers do not meet the standards. The parents want their children to be able to read and write. Regarding the needs of the Early Childhood Development Centers under Local Administrative Organizations in Chaiyaphum Province, a survey on the needs and necessities should be conducted. In terms of the budgets, cooperation with the community should be built to purchase materials and equipment as well as improve the buildings to meet the standards. Community participation should be promoted. The development guidelines for the caregivers taking care of the children in the Early Childhood Development Centers under Local Administrative Organizations should focus on the use of local wisdom and participatory action research. (2) The results of the development of the caregivers in organizing experiences to develop the IQ of early childhood children in the Early Childhood Development Centers: The caregivers have developed their knowledge and understanding. They can make use of localization to create an integrated plan to develop the intelligence quotient (IQ) of early childhood.